Does a Stewardship Code Improve the Firm Valuation and ESG Factors in India? - Amit Pandey; Anil Kumar Sharma (Australasian Accounting, Business and Finance Journal, 2024)
This is the first study from an emerging market to examine the effect of stewardship codes on the relationship between institutional investors' (IIs) ownership and firm valuation, along with environmental, social, and governance (ESG) factors3.. Using all S&P BSE listed non-financial firms data from financial years 2014-2015 to 2022-23, the results reveal a negative relationship between future firm value and II's ownership. Notably, stewardship code adoption does not affect Independent institutional investors' (IIIs)/ mutual fund (MF) ownership relationships with future firm valuation; however, Other institutional investors' (OIIs) negative relationship gets more profound. Difference in Difference (DID) analysis results confirm that the stewardship code positively affects IIs' and firm valuation relationship concerning firms with low promoter ownership than firms with high (more than 50%) ownership. However, the effect of the stewardship code changes throughout the different levels of Tobin Q. We find that an increasing IIs ownership enhances the likelihood of a positive change in ESG and its factors in which the environmental (E) factor contributes substantially . Further, a positive change in the governance score is associated with other institutional investors' (OIIs) ownership. Adopting the stewardship code strengthens the association between MF ownership and ESG factors.
Keywords: Institutional Investors ownership; ESG factors; Firm Value; Stewardship Code; Corporate Governance